2012
DOI: 10.1084/jem.20110540
|View full text |Cite
|
Sign up to set email alerts
|

A novel murine model of myeloproliferative disorders generated by overexpression of the transcription factor NF-E2

Abstract: Mice expressing a transgene encoding the transcription factor NF-E2 in hematopoietic cells exhibit features of myeloproliferative neoplasms, including thrombocytosis, Epo-independent colony formation, stem and progenitor cell overabundance, leukocytosis, and progression to acute myeloid leukemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
78
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(85 citation statements)
references
References 69 publications
3
78
1
Order By: Relevance
“…[2][3][4] Transgenic and knock-in mice expressing mutant JAK2 have provided compelling evidence that mutated JAK2 (typically JAK2-V617F) is a driver in this major subset of myeloproliferative neoplasms, however these mice are poor models for PMF. 5 PMF characteristics such as megakaryocyte proliferation and fibrosis have been recapitulated in mice expressing thrombopoietin, 6 the NF-E2 transcription factor, 7 vascular endothelial growth factor 8 or reduced levels of GATA1, 9 suggesting that abnormal erythroid/megakaryocyte development and/or abnormal release of cytokines may be a key factor in the disease. Although it has been postulated that aberrant interactions between the neoplastic cells and the BM microenvironment contribute to the distinct characteristics of PMF, 10 the underlying modifying mutation(s) in the context of the human neoplastic stem cell clone remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Transgenic and knock-in mice expressing mutant JAK2 have provided compelling evidence that mutated JAK2 (typically JAK2-V617F) is a driver in this major subset of myeloproliferative neoplasms, however these mice are poor models for PMF. 5 PMF characteristics such as megakaryocyte proliferation and fibrosis have been recapitulated in mice expressing thrombopoietin, 6 the NF-E2 transcription factor, 7 vascular endothelial growth factor 8 or reduced levels of GATA1, 9 suggesting that abnormal erythroid/megakaryocyte development and/or abnormal release of cytokines may be a key factor in the disease. Although it has been postulated that aberrant interactions between the neoplastic cells and the BM microenvironment contribute to the distinct characteristics of PMF, 10 the underlying modifying mutation(s) in the context of the human neoplastic stem cell clone remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 In a murine model, NF-E2 overexpression causes an MPN phenotype including thrombocytosis, leukocytosis, erythropoietin (Epo)-independent colony formation, characteristic bone marrow histology, expansion of stem-and progenitor compartments, and spontaneous transformation to acute myeloid leukemia. 11 This observation establishes a role for aberrant NF-E2 expression in the pathophysiology of MPN.…”
Section: Introductionmentioning
confidence: 66%
“…At the same time, however, tg mice show an increase in iron deposits in the spleen as well as elevated lactate dehydrogenase levels, strongly suggesting augmented red blood cell (RBC) destruction. 2 Taken together, these two observations could explain the absence of polycythemia in NF-E2 tg mice.…”
Section: Introductionmentioning
confidence: 80%
“…1 Patients with polycythemia vera (PV), whose lead symptom is erythrocytosis, show significantly elevated NF-E2 levels both in progenitor cells and in mature compartments. 2,3 Recently, we have shown that NF-E2 overexpression in a transgenic (tg) mouse model leads to a myeloproliferative neoplasm (MPN) phenotype characterized by thrombocytosis, leukocytosis, the expansion of stem and progenitor compartments and erythropoietin-independent colony formation. 2 In addition, NF-E2 transgenic mice presented with elevated reticulocyte counts, indicating an increased erythroid drive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation